Development and Validation of a Risk Prediction Model of Vancomycin‐Associated Nephrotoxicity in Elderly Patients: A Pilot Study. Issue 3 (9th January 2020) - Pan, Chen; Wen, Aiping; Li, Xingang; Li, Dandan; Zhang, Yang; Liao, Yin; Ren, Yue; Shen, Su
Abstract : This exploratory study aimed to develop a risk prediction model of vancomycin‐associated nephrotoxicity (VANT) in elderly patients. Clinical information of elderly patients who received vancomycin therapy from January 2016 to June 2018 was retrieved. A total of 255 patients were included in this study. Univariate analysis and multivariable logistic regression analysis revealed that vancomycin trough concentration ≥ 20 mg/L (odds ratio (OR) = 3.009; 95% confidence interval (CI) 1.345–6.732), surgery (OR = 3.357; 95% CI 1.309–8.605), the Charlson Comorbidities Index ≥ 4 points (OR = 2.604; 95% CI 1.172–5.787), concomitant use of cardiotonic drug (OR = 3.283; 95% CI 1.340–8.042), plasma volume expander (OR = 3.459; 95% CI 1.428–8.382), and piperacillin/tazobactam (OR = 2.547; 95% CI 1.680–6.007) were risk factors for VANT in elderly patients. Furthermore, a VANT risk prediction model was developed, which had good discriminative power and was well‐calibrated.